Analisis Ekranisasi antara Novel dengan Film Edensor - Intan Nurani Putri (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2023)
The researcher aims to find out the process of ecranization of the novel into film and to find out how the three are connected. Then understand the comparison of the ecranization of a novel into film as the basis for deepening the study of reviews in class XI high school. After that, the researcher aims to find out the implementation of the novel's ecranization into film in Indonesian language learning in class XI high school. The implementation of the ecranization includes analysis of shrinking, adding and varying changes. Judging from the type of data, the research approach used in this study is a descriptive qualitative research method with a structural approach to the literary works that are the object of study. Based on the analysis, it was found that the results of ecranization between the novel and the Edensor film were as follows, 1) The shrinking aspect was the most frequent finding, with 50 findings or a percentage of 49% of the total findings. 2) Then the addition aspect is in the second most order, namely with a total of 35 findings or if it is percentaged at 34.3%. 3) Then the last aspect of change varies with the findings at least with a total of 17 findings or a percentage of 16.7%.